Employing complementary spectroscopies to study the conformations of an epimeric pair of side-chain stapled peptides in aqueous solution. Issue 7 (20th January 2021) - Bogaerts, Jonathan; Atilaw, Yoseph; Peintner, Stefan; Aerts, Roy; Kihlberg, Jan; Johannessen, Christian; Erdélyi, Máté
Abstract : Spectroscopic evaluation of an epimeric pair of macrocycles identified their solution ensembles, and the conformation responsible for bioactivity. Abstract : Understanding the conformational preferences of free ligands in solution is often necessary to rationalize structure–activity relationships in drug discovery. Herein, we examine the conformational behavior of an epimeric pair of side-chain stapled peptides that inhibit the FAD dependent amine oxidase lysine specific demethylase 1 (LSD1). The peptides differ only at a single stereocenter, but display a major difference in binding affinity. Their Raman optical activity (ROA) spectra are most likely dominated by the C-terminus, obscuring the analysis of the epimeric macrocycle. By employing NMR spectroscopy, we show a difference in conformational behavior between the two compounds and that the LSD1 bound conformation of the most potent compound is present to a measurable extent in aqueous solution. In addition, we illustrate that Molecular Dynamics (MD) simulations produce ensembles that include the most important solution conformations, but that it remains problematic to identify relevant conformations with no a priori knowledge from the large conformational pool. Furthermore, this work highlights the importance of understanding the scope and limitations of the available techniques for conducting conformational analyses. It also emphasizes the importance of conformational selection of a flexible ligand in molecular recognition.